The Manifestations of Covid-19 Infection. Manifestations in Patients with Temporomandibular Joint Disorders - Machoň, Vladimír; Levorová, Jitka; Beňo, Michal; Foltán, René (Prague medical report, 2022)
The authors present a group of patients who were treated for exacerbation of temporomandibular joint disorders (TMD) following Covid-19 infection and who in the past had successfully undergone surgery of the temporomandibular joint (TMJ). The group consisted in total of 21 patients who relapsed after contracting Covid-19. There were 4 men and 17 women, the average age was 45.6 years (28-63). The most common complaint was pain. In all cases, the pain was located in the preauricular area, 4 patients had pain in the lateral side of the neck, 1 patient had pain of the nasal alae. During clinical examination, pain was present on palpation of the masseter muscle (19 patients), temporal muscle (4 patients) and the TMJ area (4 patients). In 4 cases, pain on palpation was present in the area of the nape and sternocleidomastoid muscles. Treatment in all cases was the same: thermotherapy, muscle relaxation massage and non-steroidal anti-inflammatory drugs. Symptoms subsided in all cases within 2 weeks. In light of the Covid-19 pandemic, it is also necessary to expect an increased number of patients with TMD. The authors recommend targeted patient histories regarding Covid-19 infection when examining patients with TMD symptoms - this will certainly facilitate determining the etiology of the pain.
Keywords: Pain; pandemie; Humans; Temporomandibular Joint; lidé středního věku; Female; Pandemics; lidé; Temporomandibular Joint Disorders; temporomandibulární kloub; Covid-19; COVID-19; nemoci temporomandibulárního kloubu; ženské pohlaví; Male; Middle Aged; Facial Pain; mužské pohlaví; Temporomandibular joint; obličejová bolest